A RARE CASE OF EXTERNAL EAR SKIN PLASTY WITH XENOGENIC BOVINE COLLAGEN MEMBRANE AND PLATELET-RICH PLASMA - Yanko G. Yankov; Ralitsa V. Yotsova; Lyuben L. Stoev; Simeon N. Dimanov (Journal of IMAB)
This case report highlights the successful management of a skin defect on the ear concha using a xenogenic bovine collagen membrane and platelet-rich plasma (PRP) following the excision of basosquamous carcinoma in an 89-year-old male patient. The collagen membrane, softened in saline, was precisely adapted to the defect and secured to the underlying cartilage. PRP was prepared using a double-spin centrifugation method and applied to enhance tissue regeneration. Histopathology confirmed complete excision of the carcinoma. Postoperative follow-up revealed excellent integration of the membrane, no complications, and no recurrence over one year. The case demonstrated the synergistic benefits of bovine collagen membranes and autologous PRP in restoring small postoperative skin defects, underscoring the potential for expanded applications in dermatologic surgery. Further research is recommended to assess the efficacy in larger defects and refine protocols for broader clinical use.